Osteoprotegerin independently predicts mortality in patients with stable coronary artery disease: The CLARICOR trial. (November 2014) - Bjerre, Mette; Hilden, Jørgen; Kastrup, Jens; Skoog, Maria; Hansen, Jørgen F.; Kolmos, Hans J.; Jensen, Gorm B.; Kjøller, Erik; Winkel, Per; Flyvbjerg, Allan; Gluud, Christian; The Claricor Trial Group
Abstract Objectives. To elucidate the prognostic power of serum osteoprotegerin (OPG) in patients with stable coronary artery disease (CAD). Methods. Serum OPG levels were measured in the CLARICOR trial cohort of 4063 patients with stable CAD on blood samples drawn at randomization. The follow-up was 2.6 years for detailed cardiovascular events and 6 years for all-cause mortality. Results. OPG levels were significantly increased in non-survivors (21%) compared to survivors (median [quartiles] 2092 ng/L [1636; 2800] compared to 1695 ng/L [1322; 2193, p < 0.0001]). The 2.6-year follow-up showed that OPG adds to the prediction of both cardiovascular and all-cause mortality in combination with clinical risk factors (HR [one log10 unit increase] 6.1 [95% CI 2.4–15.6, p = 0.0001]) and HR 6.5 [95% CI 3.4–12.5, p < 0.0001], respectively). Similar, in the 6-year follow-up, OPG was found to be a strong predictor for all-cause mortality. Importantly, OPG remained an independent predictor of mortality even after adjustment for both clinical and conventional cardiovascular risk markers (HR 2.5 [95% CI 1.6–3.9, p < 0.0001]). Conclusions. Serum OPG has a long-lasting independent predictive power as to all-cause mortality and cardiovascular death in patients with stable CAD.